“TO ME, THE POOR AND THE POWERLESS – AND I AM THAT – ARE ALWAYS THE ONES THAT KNOW WHAT IS GOING ON” - INTERVIEW WITH IRISH WRITER EMER MARTIN - Terrazas Gallego, Melania (Inventário, 2020)
Emer Martin is an Irish author, artist and teacher who lives in California. She has produced a strikingly diverse range of work: novels, poems, literary journalism, paintings, and short films. She is also an active writer for newspapers and on social media. Her first novel, Breakfast in Babylon (1995), won Book of the Year 1996 at the prestigious Listowel Writers’ Week in her native Ireland. This novel and her next, More Bread Or I’ll Appear (1999), were published internationally and widely acclaimed. Her third novel, Baby Zero, was published in the UK and Ireland in March 2007 by Dingle, and released in the US in 2014 by Rawmeash, an artist-led publishing cooperative run by artists for artists and based between USA and Ireland. Rawmeash was founded by Emer Martin in 2012. Emer Martin is an extremely political and expressive artist. In this interview, she shares her views on such cultural matters and the idea of art as resistance; or contemporary concerns, such as the politics of capitalism, the COVID-19 crisis or climate change. She also argues about her latest novel, The Cruelty Men, which in 2019 was shortlisted for best Irish novel the same year.